Throughput Improving Model for Patients with Chest Pain in Heart Emergency Department - Mohammad Mehdi Sepehri; Sara Naderi; Mansoureh Naderi (Tehran University of Medical Sciences, 2017)
Background and Aim: Throughput improvement is a process that simultaneously increases the volume of services provided to patients, while decreasing the operating costs. The aim of the present study was to extract and prioritize the factors affecting throughput in an emergency department for heart disease patients. Materials and Methods: This is a descriptive case study conducted through: interviews with experts, and the design of a questionnaire based on the emergency management criteria specified by the Ministry of Health and Medical Education (MOHME), and the completion of the questionnaire by academic experts in a teaching hospital in Tehran.  Six indicators and 26 sub-indicators were extracted and the data was analyzed using multi- criteria decision analysis methods including ANP and DEMATEL. Results: Among the 26 sub-indicators, six sub-indicators were identified as the top priority ones with a 72 percent impact on throughput. And out of the six top indicators, cardiac emergency clinical guidelines were identified as the most important in maximizing throughput for patients with chest pain in the emergency department under study.  Conclusion: This study identified the priorities in enhancing throughput in an emergency cardiac unit. For the first time in Iran the study used a hybrid  ANP-DEMATEL method. This study can provide insights for health system planners and policy-makers on the enhancement of throughput in care delivery  organizations, especially teaching hospitals.